ROLE OF RADIOGRAPHER IN HANDLING COVID-19 AT CT SCAN ROOM DURING PANDEMIC - Mardliyyah, Aisyatun; Sensusiati, Anggraini Dwi; Sari, Amilia Kartika (Faculty of Vocational Studies, Universitas Airlangga, 2020)
Background: Radiographers have a big role in handling COVID-19 during the pandemic. Radiographers not only play an important role in making good diagnostic images, but also in efforts to prevent infection transmission, especially in the CT scan room. Purpose: To compile and summarize role of radiographer in handling COVID-19 at CT scan room during pandemic. Method: The method used is literature study. Sources of data used are observations and summaries of various literature from a collection of journals selected according to predetermined criteria and then presented descriptivel/narratively. Result: Role of radiographer in handling COVID-19 at CT scan room during pandemic from various journals. Conclusion: Role of radiographer includes setting the area and staff, preparing for the examination, conducting the examination, the level of PPE use, cleaning and disinfection methods and treating medical waste.